A theory of demand for gambles - John A. Nyman (University of Minnesota, Center for Economic Research, 2004)
Although gambling is primarily an economic activity, no single theory of the demand for gambles has gained wide-spread acceptance among economists. This paper proposes a simple model of the demand for gambling that is based on the standard economic assumptions that (1) resources are scarce and (2) consumers utility increases with income at a decreasing rate. This model has the advantages that (1) it is based solely on changes in income, (2) is potentially applicable to most consumers, (3) preserves the assumption of diminishing marginal utility of income, (4) is consistent with the insurance-buying gambler, and (5) has intuitive appeal.
Keywords: D81; D11; 330; gambling; demand for gambles; expected utility theory